From Environmental Clicktivism to Trash Cleanup : New Initiative of Instagram Account @Pandawaragroup - Desy Erika; Akhmad Roqi Alawi (Universitas Multimedia Nusantara, 2024)
Environmental awareness movements on social media are often limited to